PERSPECTIVES ON TEACHING AND LEARNING: INSIGHTS OF THAI STUDENT TEACHER TRAINEES' OBSERVATIONS IN UITM KEDAH - Razanawati Nordin; Nur Syazwanie Mansor; Rafidah Amat; Nadira M. Jahaya; Fatin Rahaina Ahamd Sani; Azlan Abdul Rahman, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This paper explores the observations and insights of Thai student teacher trainees during their practicum at UiTM Kedah, Malaysia. Through a qualitative analysis of their experiences, the study examines their perspectives on teaching methodologies, classroom management, cultural integration, and overall professional development. By employing a thematic analysis of their reflections, we uncover their perspectives on various teaching methodologies, classroom management techniques, cultural integration, and professional growth. The findings reveal a complex view of educational practices and highlight the benefits of cross-cultural exchange in enhancing teaching competencies and fostering a deeper understanding of pedagogical approaches.